Hypotenuse=base×base+hieght×height Base=hypotenuse×hypotenuse -height ×height Height=base×base - hypotenuse×hypotenuse
The pythagoras' theorem states that the square of the hypotenuse is equal to the sum of the square of the other 2 sides. The equation would be hyp2=S12+S22 note: the 2 is the power of two
AB2+BC2=AC2 THIS MEANS THAT IN A TRIANGLE WHEN WE ADD THE SQUARE OF THE BASE AND PARALLEL ANGLE IT WILL ALWAYS BE EQUAL TO THE HYPOTENUSE.
a = 1 side, b = another side, c = hypotenuse (the longest side). The formula is: a2 + b2 = c2 (the two means squared, not multiplied by two). The formula only works in right-angled triangles.